Investigating the relationship among service quality, emotional satisfaction and favorable behavioral intentions in higher education service experience - Wan Mustaffa, Wan Salmuni; Ali @ Hamid, Mass Hareeza; Khuan, Wai Bing; Abdul Rahman, Rafiduraida (2016)
Most previous research has examined the direct relationship between service quality (SQ) and favorable behavioral intentions (FBI), neglecting the important role of emotional satisfaction (E-SAC). E-SAC is viewed as a crucial indicator in enhancing the relationship between SQ and FBI. It also assists the service provider in higher education to build long-term relationships with students. Thus, the main objective of this research is to examine the relationship among SQ, E-SAC and FBI. This research was conducted at Malaysian Public Universities. The online questionnaire was distributed to 381 international students following the stratified random sampling. The Structural Equation Modeling (SEM) technique using AMOS software was performed to test the relationship among SQ, E-SAC and FBI. The finding reveals that E-SAC mediates the relationships between SQ and FBI with large effects size. This research also discusses the theoretical and practical implications as well as the direction for future research.